(3GdEbJUGO GdGOGQjs - (3eMehO MSjf(B, (3GdhGOjs; (3GSeGYjd jhfS jGejf hBNQhf(B, s ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B,s, 2010)
(3ebOeI Yf GdGbJUGO GdGOGQj(B- (3JMdjd GdWdH hGdGjQGOGJ(B- (3fXQjI GdefTCI(B- (3fXQjI GdGfJGL(B- (3JMdjd JcGdja GdGfJGL hGdYQV(B- (3SjGSGJ GdJSYjQ hbQGQGJ GdGfJGL(B- (3JMdjd GdGQHGM hGdbQGQGJ GdGOGQjI(B- (3GdJQcjR hGdGfOeGL hGdJcGed Hjf GdeTQhYGJs
Keywords: (3EOGQI GdCYeGds; (3GdEbJUGOs